Method for determining angles in X-ray emulsion chambers (XRECs) (ADRON experiment) (Physical Sciences and Technology, 2019)
Paper presents an analysis of the measurement procedure of the zenith and azimuth angles υ and φ in theX-ray emulsion chambers (XREC) of ADRON and PAMIR experiments. Earlier, asymmetry wasobserved in distributions of azimuth angles of gamma and hadron families. A detailed analysis ofmethodological errors in measuring θ, φ angles allowed us to establish the causes of the distortion ofazimuth angles distributions. There are two reasons: systematic errors in the measurement of zenithangles by MBS-2 microscopes, used both in the PAMIR experiment, and in the ADRON experiment, andthe inclination of XREC based on the subsidence. Calculations showed that the total systematic errorΔυ≈4 ° completely explains the observed azimuthal asymmetry. Formulas for correcting θ and φ anglesare given. The recalculation of the angles by the indicated formulas showed that this corrects thedistribution of the azimuthal angles φ. The REC plane should be set relative to the horizontal with anaccuracy of no worse than 1 degree in order to avoid distortion of the angular distributions.